Transfers to Families with Children as a Principal-Agent Problem - Alessandro Cigno; Annalisa Luporini; Anna Pettini (Center for Economic Studies and ifo Institute (CESifo), 2000)
The relationship between government and parents is modelled as a principal-agent problem, with the former in the role of principal and the latter in the role of agents. We make three major points. The first is that, if the well-being of the child depends not only on luck, but also on parental actions that the government cannot readily observe, the latter can influence parental behaviour indirectly, by conditioning transfers on performance. The second point is that, if there are market inputs into the making of a happy or successful child, which the government can observe, but cannot ascribe to any particular parent or child because they are bought anonymously, an income transfer policy can be usefully complemented by an indirect tax policy that systematically distorts prices in favour of these inputs. The third is that, if parents care about their children, insurance and incentive considerations must be tempered by the need to compensate parents who have the misfortune of getting a child with low ability or, more generally, less well equipped to make the most of life. Ways of making these findings operative are discussed in some detail.
Keywords: 330